Absicoccus porci gen. nov., sp. nov., a member of the family Erysipelotrichaceae isolated from pig faeces. Issue 2 (8th November 2019) - Shin, Yeseul; Paek, Jayoung; Kim, Hongik; Kook, Joong-Ki; Kim, Joong-Su; Kim, Si Hyun; Chang, Young-Hyo
Abstract : An obligately anaerobic, Gram-stain-positive and coccus-shaped bacterium, designated strain YH-panp20 T, was isolated from pig faeces. Phylogenetic analysis based on 16S rRNA gene sequencing indicated that the isolate belongs to the family Erysipelotrichaceae, and is most closely related to Catenisphaera adipataccumulans KCTC 15517 T (93.5 % sequence similarity), followed by Faecalitalea cylindroides KCTC 5815 T (92.2 %), Faecalicoccus acidiformans KCTC 15521 T (90.2 %) and Holdemanella biformis KCTC 5969 T (89.6 %). Average nucleotide identity values between YH-panp20 T and its closest relatives were lower than 71 %. The G+C content of the isolate was 38.4 mol%, and its cell-wall peptidoglycan was found to be of A1γ type and contained meso -diaminopimelic acid. The predominant fatty acids were C18 : 1 cis 9, C18 : 0 DMA and C16 : 0 . The major end-products of glucose fermentation were lactate, acetate and formate. Therefore, based on the phenotypic, phylogenetic and chemotaxonomic properties, a novel genus and species, Absicoccus porci gen. nov., sp. nov., is proposed for isolate YH-panp20 T (=KCTC 15747 T =JCM 32769 T ).